The relationship between MT and LXX in Jeremiah 39(46):1-41(48):3 and 52 - Frohlich, James (Forschungen zum Alten Testament / 2, 2022)
"In this work, James Frohlich analyzes the Septuagint translation technique in Jeremiah 39(46)-41(48):3 and 52 in order to determine if the large-scale differences between MT and LXX in these chapters were caused by the LXX translator. Since the Hebrew text of Jeremiah 52 largely parallels that of 2 Kings 24:18-25:30, and Jeremiah 39(46)-41(48):3 has various parallels with 2 Kgs 25:22-26, the author also focuses on the differences between the Septuagint translations in these parallel texts. Along with a study of translation technique, he also considers the nature of the MT pluses and analyzes the agreements and disagreements between Jeremiah 39(46)-41(48):3 and 52 MT/LXX with the parallel text in 2 Kings 24:18-25:30 MT/LXX. James Frohlich concludes that the large-scale differences between MT and LXX in Jeremiah 39-41:3 and 52 are due to a divergent Hebrew Vorlage used by the Septuagint translator."